2015
DOI: 10.1002/app.42409
|View full text |Cite
|
Sign up to set email alerts
|

A novel hydrogen peroxide sensor based on Ag nanoparticles decorated polyaniline/graphene composites

Abstract: A novel electrochemical sensor based on Ag nanoparticles (AgNPs) decorated polyaniline/graphene composites (PANI/G) is developed, which can be used for sensitive determination of H 2 O 2 . For the construction of the H 2 O 2 sensor, polyaniline (PANI) is first electrodeposited on the surface of graphene (G) to form PANI/G, and then horseradish peroxidase (HRP) loaded on AgNPs (HRP/AgNPs) is immobilized on to the PANI/G. H 2 O 2 can be catalyzed by HRP to generate current response which can be significantly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The superior sensing performance of GOx/Au/MXene/Nafion/GCE is attributed to the improvement in the relative activity of GOx in the presence of Au nanoparticles. It has been widely reported that the biosensing properties of graphene-based sensors can be dramatically improved by anchoring Au nanoparticles on the surface of graphene nanosheets5354555657. In a similar way, dispersion of Au nanoparticles on the surface of MXene nanosheets is expected to improve the electrical conductivity and makes the resultant Au/MXene composite as a better electrochemical transducer/enzyme immobilization matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The superior sensing performance of GOx/Au/MXene/Nafion/GCE is attributed to the improvement in the relative activity of GOx in the presence of Au nanoparticles. It has been widely reported that the biosensing properties of graphene-based sensors can be dramatically improved by anchoring Au nanoparticles on the surface of graphene nanosheets5354555657. In a similar way, dispersion of Au nanoparticles on the surface of MXene nanosheets is expected to improve the electrical conductivity and makes the resultant Au/MXene composite as a better electrochemical transducer/enzyme immobilization matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the previously reported studies for H 2 O 2 was disclosed (Table1). Comparing with various non‐enzymatic H 2 O 2 sensors in Table1, the Cu 2 O/ERGO nanocomposites possessed desirable detection limit and a wide linear response range (0.001–1.0 mM) at applied potential of −0.25 V . As can be seen in Table , the Cu 2 O/ERGO nanocomposite‐modified electrode can be preferred for amperometric detection of H 2 O 2 with low LOD.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Graphene derivatives such as graphene oxide and reduced graphene oxide and their nanocomposites have also been extensively studied for various electronic and environmental applications. 2,18–22 However, the processability conditions for the direct use of pure graphene sheets are challenging due to their hydrophobic character. 23 Therefore, efficient strategies are needed to utilize graphene in its natural form and without any chemical modification.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a GCE modified with a Ag nanoparticle-decorated polyaniline/graphene composite showed promising sensing activity against H 2 O 2 with a detection limit of 0.03 mM in 0.1 M PBS at pH 7.0. 19 Similarly, a Pt nanoparticle ensemble on a PANI/G composite was drop-cast on a GCE and used for H 2 O 2 sensing in 0.1 M PBS and exhibited a detection limit of 50 nM. 25 Due to the effectiveness of the process and the low detection limits, the research on graphene-based electrochemical sensors for H 2 O 2 sensing is open for new strategies.…”
Section: Introductionmentioning
confidence: 99%